Stratigraphy, Facies, and Chemostratigraphy at the Palaeoproterozoic Rävliden North Zn-Pb-Ag-Cu VMS deposit, Skellefte district, Sweden - Simán, Filip; Jansson, Nils; Liwicki, Foteini; Nordfeldt, Erik; Fjellerad Persson, Mac; Albrecht, Lena; Günther, Christian; McDonnell, Paul; Hermansson, Tobias (Ore Geology Reviews, 2025)
Many base and precious metals are sourced from volcanic massive sulphide (VMS) deposits and understanding the geological characteristics of such deposits is crucial for new discoveries of this deposit type. Although key geological characteristics of modern VMS systems are relatively well understood, a remaining challenge is resolving the same geological characteristics in ancient, complex, altered and metamorphosed VMS deposits. One such deposit is the Palaeoproterozoic Rävliden North deposit, an 8.7 Mt (combined resources and reserves of 3.42 % Zn, 0.90 % Cu, 0.54 % Pb, 81 g/t Ag, and 0.24 g/t Au) replacement-style volcanic massive sulphide deposit in the felsic-bimodal western Skellefte district, northern Sweden. The VMS deposits in the Skellefte district are hosted in rocks subjected to greenschist to amphibolite facies metamorphism and occur at the lithostratigraphic contact between the metavolcanic 1.89 – 1.88 Ga Skellefte group (SG) and stratigraphically overlying metasiliciclastic 1.89 – 1.87 Ga Vargfors group (VG). Intense hydrothermal alteration commonly eradicates original rock textures, and polyphase deformation and metamorphism make geological interpretation and stratigraphic reconstruction difficult. Hence, to complement lithofacies analysis, immobile element chemostratigraphy is used in this study. Rävliden North is predominantly hosted by felsic volcanic rocks of the herein defined Rävliden formation in the upper part of the SG that were deposited in half grabens related to rifting of a continental arc. Based on immobile elements and their ratios the felsic rocks fall into three groups, Rhy I, II and III. The chemostratigraphy and lithostratigraphy roughly coincide, where Rhy II (Zr/Al2O3 = 12.86, Al2O3/TiO2 = 36.07, Zr/TiO2 = 0.05) defines the rhyolites beneath the Rävliden formation that predominantly comprises Rhy I (Zr/Al2O3 = 17.23, Al2O3/TiO2 = 32.33, Zr/TiO2 = 0.06) and Rhy III (Zr/Al2O3 = 17.95, Al2O3/TiO2 = 36.53, Zr/TiO2 = 0.07), where Rhy I is the chief host to mineralisation. ...